2016
DOI: 10.1002/dc.23531
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline globules and papillary fragments in cytologic smears from two intra‐abdominal tumors (ovarian and hepatic) in female patients: A diagnostic pitfall with histologic correlation

Abstract: Hyaline globules and papillary fragments in cytologic samples from two intra-abdominal tumors in young females are presented including the cytological features and the correlation with the histopathologic and immunohistochemical findings. In the first case a cytologic study from an ovarian mass showed papillary structures and isolated tumor cells with epithelioid morphology, irregular reniform-like nuclear contour, pale or vacuolated cytoplasm, abundant hyaline globules and occasional glomeruloid structures re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Next, clear cell features were the most frequently detected in METex14 but evenly distributed throughout the other alterations, except for mutated BRAF and MAP2K1 and rearranged RET . Furthermore, we showed that LAD with METex14 frequently exhibited intracytoplasmic hyaline globules that have been associated with various neoplasms, such as a yolk sac tumour or clear cell carcinoma of gynaecological origin, hepatocellular carcinoma, solid pseudopapillary neoplasm of the pancreas and renal cell carcinoma, some of which exhibit concurrent clear cell change of carcinoma cells 25‐27 . Hyaline globules in all locations, tumour types including LADs, 28 or any specific pathological process showed the same ultrastructural features, i.e.…”
Section: Discussionmentioning
confidence: 75%
“…Next, clear cell features were the most frequently detected in METex14 but evenly distributed throughout the other alterations, except for mutated BRAF and MAP2K1 and rearranged RET . Furthermore, we showed that LAD with METex14 frequently exhibited intracytoplasmic hyaline globules that have been associated with various neoplasms, such as a yolk sac tumour or clear cell carcinoma of gynaecological origin, hepatocellular carcinoma, solid pseudopapillary neoplasm of the pancreas and renal cell carcinoma, some of which exhibit concurrent clear cell change of carcinoma cells 25‐27 . Hyaline globules in all locations, tumour types including LADs, 28 or any specific pathological process showed the same ultrastructural features, i.e.…”
Section: Discussionmentioning
confidence: 75%